Effect of aqueous polymer treatments on wood properties part 11: mechanical properties - Ashaari, Z.; Barnes, H. M.; Lyon, D. E.; Vasishth, R. C.; NicholasD. D., D. D. (1990)
Partially air-dried sapwood of sweetgum (Liquidambar styraciflua) and southern pine (Pinus spp.) was treated with either aqueous polyacrylate or aqueous dimethyloldihydroxyethyleneurea (DMDHEU) solutions. Tests for static bending, toughness, and hardness were conducted on matched treated and untreated pieces according to ASTM Standards. Properties of pine were not affected by treatment with the polyacrylate .. With sweetgum, the modulus of rupture and modulus of elasticity were reduced, while hardness was improved. For the DMDHEU treatment, reduction in property values for both species was related to curing temperature.